Coptidis Rhizoma: a comprehensive review of its traditional uses, botany, phytochemistry, pharmacology and toxicology - Jin Wang; Lin Wang; Guan-Hua Lou; Hai-Rong Zeng; Ju Hu; Qin-Wan Huang; Wei Peng; Xiang-Bo Yang (Taylor & Francis Group, 2019)
Context: Coptidis rhizome (CR), also known as Huanglian in Chinese, is the rhizome of Coptis chinensis Franch., C. deltoidea C.Y. Cheng et Hsiao, or C. teeta Wall (Ranunculaceae). It has been widely used to treat bacillary dysentery, diabetes, pertussis, sore throat, aphtha, and eczema in China. Objectives: The present paper reviews the latest advances of CR, focusing on the botany, phytochemistry, traditional usages, pharmacokinetics, pharmacology and toxicology of CR and its future perspectives. Methods: Studies from 1985 to 2018 were reviewed from books; PhD. and MSc. dissertations; the state and local drug standards; PubMed; CNKI; Scopus; the Web of Science; and Google Scholar using the keywords Coptis, Coptidis Rhizoma, Huanglian, and goldthread. Results: Currently, 128 chemical constituents have been isolated and identified from CR. Alkaloids are the characteristic components, together with organic acids, coumarins, phenylpropanoids and quinones. The extracts/compounds isolated from CR cover a wide pharmacological spectrum, including antibacterial, antivirus, antifungal, antidiabetic, anticancer and cardioprotective effects. Berberine is the most important active constituent and the primary toxic component of CR. Conclusions: As an important herbal medicine in Chinese medicine, CR has the potential to treat various diseases. However, further research should be undertaken to investigate the clinical effects, toxic constituents, target organs and pharmacokinetics, and to establish criteria for quality control, for CR and its related medications. In addition, the active constituents, other than alkaloids, in both raw and processed products of CR should be investigated.